Analisis Bibliometrik tentang Tren dan Pemetaan Tema Penelitian Media Lift The Flap Book dalam Pembelajaran Numerasi Anak Usia Dini - Andik Rahmatiah; Yeni Rachmawati (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze research trends and map thematic developments related to the use of lift-the-flap books in early childhood numeracy learning during the 2020-2025 period using a bibliometric analysis approach. Data were retrieved from Google Scholar using the Publish or Perish application and analyzed with VOSviewer to map keyword networks, temporal trends, and thematic density. The findings indicate that research publications fluctuated over the study period and demonstrated dynamic thematic development. The thematic mapping identified six major clusters and revealed a shift in research focus from the introduction of numerical symbols toward studies of learning processes, children’s learning experiences, and the role of educators. The novelty of this study lies in its systematic mapping of the structure and developmental trajectory of research on lift-the-flap books in early childhood numeracy learning, providing theoretical contributions as well as practical implications for future research and the development of instructional media in early childhood education.